PRAKTIK GADAI SAWAH DI MASYARAKAT : TINJAUAN HUKUM DAN ETIKA - Febri Atikawati Wiseno Putri,; Febrianti Kusuma Astuti,; Arga Baskara, (Journal of Innovation Research and Knowledge, 2025)
The practice of paddy field pawning is still a prevalent phenomenon in Indonesian rural communities, despite the existence of regulations governing it. The practice of paddy field pawning from a legal and ethical perspective, and formulate recommendations for the protection of the rights of the parties involved. The results showed that the practice of paddy field pawning is often not in accordance with applicable legal provisions, especially regarding the time limit and mechanism for returning the pawned land. From an ethical perspective, gadai sawah raises moral dilemmas related to justice, transparency, and the economic sustainability of rural communities. Although it provides a short-term solution, this practice has the potential to perpetuate economic inequality. This research recommends a comprehensive approach in addressing the issue of gadai sawah, including: (1) revision and strengthening of regulations by considering socio-economic conditions and local wisdom; (2) development of alternative financing products by formal financial institutions that better suit the needs of rural communities; (3) expansion of financial education and literacy programmes; (4) economic empowerment of village communities through the development of BUMDes and agricultural cooperatives; and (5) further research on alternative models of agricultural financing.The implementation of these recommendations is expected to improve legal and ethical protection in the practice of paddy field pawning, as well as contribute to the improvement of welfare and socio-economic justice in Indonesia's rural communities.